Difficulties in Differentiating Natural from Synthetic Alkaloids by Isotope Ratio Monitoring using 13C Nuclear Magnetic Resonance Spectrometry - Robins, Richard J.; Romek, Katarzyna M.; Grand, Mathilde; Nun, Pierrick; Diomande, Didier; Julien, Maxime; Remaud, Gérald S. (Planta Medica, 2018)
Within the food and pharmaceutical industries, there is an increasing legislative requirement for the accurate labeling of the productʼs origin. A key feature of this is to indicate whether the product is of natural or synthetic origin. With reference to this context, we have investigated three alkaloids commonly exploited for human use: nicotine, atropine, and caffeine. We have measured by 13C nuclear magnetic resonance spectrometry the position-specific distribution of 13C at natural abundance within several samples of each of these target molecules. This technique is well suited to distinguishing between origins, as the distribution of the 13C isotope reflects the primary source of the carbon atoms and the process by which the molecule was (bio)synthesized. Our findings indicate that labeling can be misleading, especially in relation to a supplied compound being labeled as “synthetic” even though its 13C profile indicates a natural origin.
Keywords: NMR; alkaloid; nicotine; atropine; caffeine; synthetic; natural